Plectranthus anamudianus (Lamiaceae): a new species from Western Ghats, India - Smitha, Kokkaraniyil; Sunojkumar, Purayidathkandy (Phytotaxa, 2016)
A new species, Plectranthus anamudianus (Lamiaceae) is described and illustrated from southern Western Ghats, India. The new species is similar to Plectranthus glabratus, in its inflorescence architecture but differs mainly by its habit, internode length, leaf size and shape, petiole length and texture, number of flowers per cyme, bract structure and recurved fruiting calyx. Detailed description, illustration, photographs, IUCN red list category, distribution map, notes on biogeography and other relevant notes are provided. Surface sculpturing pattern of pollen grains and mericarps of the two species are also compared.